Comparativo dos custos de sistemas construtivos em concreto armado e alvenaria estrutural- estudo de caso em Santana do Livramento/RS - Machado Junior, Asdrubal Loredo (2014)
With the expansion of the civil construction in Brazil and the increasingly fierce competition between the entrepreneurs the search for alternatives that somehow assist in executive economy to provide greater competition between companies is needed. The building typology that is used on a larger scale in comparison to any other constructive model is the reinforced concrete but, at about three decades, structural masonry has been occupying an important place as an optional constructive model, mainly in social nature's dwellings currently in large scale in the country. This paper presents a comparison of costs from established comparative indices (structure, sealing and coating) between the conventional model of reinforced concrete and structural masonry. To develop it, a case study from a sixstorey building running on conventional constructive model of reinforced concrete in the city of Santana do Livramento was done. The analysis was done from the standard floor being established that the basements and piles are common to both constructive models and that effectively, from the bandejão in structural masonry model, we will have relevant indexes to compare costs. To calculate the structural masonry ceramic blocks were used. The comparative study was done from the quantitative survey of the items that integrate the established indexes for the two constructive models, taking into consideration the peculiar characteristics of each one, mainly for the established region to develop this case study (obtaining of some inputs and labor). The analysis was based on the unitary costs of construction for the conventional structure in reinforced concrete and structural masonry. Cost analysis of the inputs, compared on the analysed subsystems for the two constructive typologies, pointed out that the constructive model of structural masonry presents, in these inputs (structure, sealing and coating) a 36,20% savings in relation to the constructive model in reinforced concrete. In this study, considering that the compared inputs represent approximately 30% of the total cost of the construction, the final economy is 10,85% in relation to the total cost.